Education-Conditioned Foreign Direct Investment and Sustainable Development: A Complementarity Perspective - Nha, Nguyen Thanh; Linh, Nguyen Tran Xuan (International Journal of Energy Economics and Policy, 2026)
This study examines the relationship between foreign direct investment and sustainable development from a complementarity perspective, emphasizing the conditioning role of education. While foreign direct investment is often viewed as a catalyst for development, its contribution to sustainable development remains highly heterogeneous across countries. Drawing on the absorptive capacity framework, the study argues that foreign direct investment enhances sustainable development only when host economies possess sufficiently strong educational foundations. Using panel data for 72 countries over the period 2008–2022, the analysis employs a hierarchical Bayesian modeling approach to account for unobserved cross country heterogeneity and interaction effects. Sustainable development is measured using the Sustainable Development Goals Index, capturing economic, social, and environmental dimensions. The empirical model includes foreign direct investment, education, their interaction, and key macroeconomic and institutional controls. The results show that foreign direct investment does not promote sustainable development when considered in isolation and may even exert adverse effects. In contrast, education has a robust positive association with sustainable development. Most importantly, the interaction between foreign direct investment and education is positive and statistically meaningful, particularly in middle income and low income countries.